Extreme skydiving - Waring, Rob.; National Geographic Society (U.S.) (Boston, Mass. : Heinle, Cengage Learning, 2010)
Most people enjoy the sport of sky diving because they get to fall at extremely high speeds, but some people want to go even faster. One man is even experimenting with various methods of increasing his speed. What is he doing to go faster? Is it working?
Footprint reading library with video from National Geographic--Cover
language bookfair2015
Keywords: Englischunterricht; Readers (Adult); English language -- Study and teaching -- Readers